Designing a Surveillance System, Temperature and Humidity Detection based on Internet of Things (IoT) in the Server room University of PGRI Adi Buana Surabaya - Dwi Hastuti; Anggarda Saputra Wijaya (BEST, 2023)
University of PGRI Adi Buana Surabaya is a university located in Surabaya, East Java. All data management processes and academic information systems are connected to the server via a local network and the internet. Currently there are three server rooms owned by the University, namely: the main Server room in the PGSD Building, second floor; Backup Server room in the Postgraduate building, third floor; and network Server room in the Ngagel campus, building a, second floor. The server room accommodates network equipment and database servers require temperature and humidity that are always maintained and routinely need to be checked by officers. To avoid damage to the server and network devices in the server room, a temperature and humidity detection system based on the Internet of Things (IoT) is made. This system is built using Home Assistant as an application of Internet of Things (IoT) centralized control system and CCTV to display conditions in real-time in each server room. Sensor to detect temperature and humidity using the DHT11 Sensor, the ESP8266 Microcontroller acts as a link between the host and the sensor by utilizing a wireless network. This tool can provide benefits in the field of Information Technology and Data in terms of monitoring so that it officers can check anytime and anywhere through a Web Service.